Pomar em escola rural como espaço de educação multidisciplinar no município de Paragominas, Pará - COUTINHO, Alessandra Lima (2021)
Actions developed in the school environment should encourage local and regional sustainability, directly interfering with social and cultural aspects. In the meantime, the school with an educational role is necessary to motivate children to participate in multidisciplinary activities that develop awareness of environmental conservation as a fruitful orchard inserted in the school space. A fruitful orchard in the school environment aims to further strengthen agriculture in rural areas, as many students come from family properties and thus create ways for teachers to be engaged in this activity as well, as some come from the city to teach in the area. rural, having little knowledge about this area. In this sense, the objective of this study was to implement a didactic fruitful orchard in the Municipal Elementary School Alegria do Saber, as a multidisciplinary education space in the city of Paragominas - PA. The method used in this research is discursive investigative, based on a case and field study on the implementation of a didactic orchard in a rural school. The project to implement the educational orchard was developed from October 2019 to March 2021, with the following steps: Implementation of the orchard (Land clearing; Area Preparation and Soil Analysis; Species Choices and Seedling Preparation; Soil correction, planting and cultural treatments); Technical training in managing the school orchard and; Focus group on the evaluation of the implantation of the school orchard in the community. The physical space of the school orchard with fruit trees, as a product generated by the master's research, introduced in the school's political-pedagogical project an inter and multidisciplinary and interdisciplinary approach for teachers, contributing to improve pedagogical practices and plural education for the community, in addition to guaranteeing a diversified school lunch, rich in vitamins provided by the cultivation of fruits. It was possible to promote the training of the school community on orchard management techniques, which served not only for the care of fruit trees at school, but also enabled the extension of learning, through techniques that will serve in the daily lives of students and parents. The experience becomes a fundamental pillar for the propagation of environmental education within the school unit, which now has a specific space where students can develop inter and multidisciplinary learning activities.